Seed germination under osmotic stress across different wild populations of mountain rye (Secale strictum (C.Presl) C.Presl)). (4th March 2022) - Rossi, Graziano; Guzzon, Filippo; Bickler, Charlotte; Cauzzi, Paolo; Di Martino, Luciano; Di Cecco, Valter; Domina, Gianniantonio; Gargano, Domenico; Vagge, Ilda; Orsenigo, Simone; Müller, Jonas V.
Abstract: The selection of resilient cultivars could help stem the losses in forage production due to a changing climate. Secale strictum is a wild grass with interesting potential as a forage crop. We studied the germination requirements of six wild S. strictum populations, representative of the whole species distribution range in Italy and occurring under different osmotic conditions (0 MPa, −0.8 MPa, −1.0 MPa, −1.2 MPa, −1.4 MPa and −1.6 MPa). Our aim was to find beneficial seed and germination traits for the possible use of this species as a crop. Different accessions of domesticated Secale cereale and × Triticosecale were used as comparison. Some populations of S. strictum were drought tolerant at germination level (final germination > 25% at −1.6 MPa). A great variability was observed among wild populations in traits that currently limit the cultivation of the species as a forage crop (seed size, germinability) and that could improve its usage, especially in arid areas (water stress tolerance, fast germination). A correlation exists between the germination rates of wild populations and the seasonality of the rainfall at their natural growing sites. These results underline the importance of choosing appropriate source lineages when selecting S. strictum populations for crop development.